2011
DOI: 10.1083/jcb.201108121
|View full text |Cite
|
Sign up to set email alerts
|

Cdc6 expression represses E-cadherin transcription and activates adjacent replication origins

Abstract: The Cdc6 replication licensing factor acts as a molecular switch at the E-cadherin locus, leading to E-cadherin transcriptional repression and local activation of replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 59 publications
4
100
0
5
Order By: Relevance
“…It has been established that Cdc6 regulates pre-replication complex assembly mainly by recruiting the Mcm2-7 helicase to DNA replication origins, licensing replication initiation (Donovan et al, 1997;Liang and Stillman, 1997;Yan et al, 1998). It is also worth mentioning that two studies have revealed that Cdc6 represses Ecadherin locus or INK4/ARF locus transcription by binding to the promoter of these genes, inspiring the notion that Cdc6 also functions in transcription (Gonzalez et al, 2006;Sideridou et al, 2011). In this work, we found that Cdc6 localizes in the nucleolus in cycling cells at the end of mitosis and early G1 phase.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that Cdc6 regulates pre-replication complex assembly mainly by recruiting the Mcm2-7 helicase to DNA replication origins, licensing replication initiation (Donovan et al, 1997;Liang and Stillman, 1997;Yan et al, 1998). It is also worth mentioning that two studies have revealed that Cdc6 represses Ecadherin locus or INK4/ARF locus transcription by binding to the promoter of these genes, inspiring the notion that Cdc6 also functions in transcription (Gonzalez et al, 2006;Sideridou et al, 2011). In this work, we found that Cdc6 localizes in the nucleolus in cycling cells at the end of mitosis and early G1 phase.…”
Section: Discussionmentioning
confidence: 99%
“…46 The molecular mechanism(s) by which Cdc6 expression makes HF more refractory to anagen-activating signals are not known and will require further investigation. They could involve the role of CDC6 in licensing replication origins, 18 its capacity to repress transcription, [15][16][17] or a combination of both. Finally, we conclude that Cdc6 overexpression by itself is not sufficient to promote skin tumors, at least in C57BL/6 mice, but its proto-oncogenic potential is unveiled in cooperation with DMBA-induced mutations.…”
Section: Discussionmentioning
confidence: 99%
“…13 The oncogenic potential of Cdc6 had been inferred from its capacity to induce DNA replication in quiescent cells, in cooperation with cycE-CDK2 14 as well as its ability to repress the expression of Ink4/Arf [15][16] and E-cadherin. 17 Cdc6 is overexpressed in subsets of brain tumors, mantle cell lymphomas and non-small cell lung carcinomas (reviewed in ref. 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…23 The same effect of overexpressed Cdc6 was also observed in human cells. 24 This phenotype was reversed when Cdc6 expression was shut down. Notably, flow cytometric analysis in mouse (P1) and human (A549) cells overexpressing Cdc6, revealed a significant increase of cells expressing the CD24 low /CD44 high antigen phenotype (Fig.…”
Section: Cdc6mentioning
confidence: 94%